Blood Gene Signatures of Chagas Cardiomyopathy With or Without Ventricular Dysfunction. (17th December 2016) - Ferreira, Ludmila Rodrigues Pinto; Ferreira, Frederico Moraes; Nakaya, Helder Imoto; Deng, Xutao; Cândido, Darlan da Silva; de Oliveira, Lea Campos; Billaud, Jean-Noel; Lanteri, Marion C; Rigaud, Vagner Oliveira-Carvalho; Seielstad, Mark; Kalil, Jorge; Fernandes, Fabio; et al.
Abstract: Chagas disease, caused by the protozoan parasite Trypanosoma cruzi, affects 7 million people in Latin American areas of endemicity. About 30% of infected patients will develop chronic Chagas cardiomyopathy (CCC), an inflammatory cardiomyopathy characterized by hypertrophy, fibrosis, and myocarditis. Further studies are necessary to understand the molecular mechanisms of disease progression. Transcriptome analysis has been increasingly used to identify molecular changes associated with disease outcomes. We thus assessed the whole-blood transcriptome of patients with Chagas disease. Microarray analysis was performed on blood samples from 150 subjects, of whom 30 were uninfected control patients and 120 had Chagas disease (1 group had asymptomatic disease, and 2 groups had CCC with either a preserved or reduced left ventricular ejection fraction [LVEF]). Each Chagas disease group displayed distinct gene expression and functional pathway profiles. The most different expression patterns were between CCC groups with a preserved or reduced LVEF. A more stringent analysis indicated that 27 differentially expressed genes, particularly those related to natural killer (NK)/CD8 + T-cell cytotoxicity, separated the 2 groups. NK/CD8 + T-cell cytotoxicity could play a role in determining Chagas disease progression. Understanding genes associated with disease may lead to improved insight into CCC pathogenesis and the identification of prognostic factors for CCC progression.